Altered Gut Microbiota Composition in Subjects Infected With Clonorchis sinensis - Meng Xu; Meng Xu; Meng Xu; Meng Xu; Meng Xu; Zhihua Jiang; Wen Huang; Jianhai Yin; Jianhai Yin; Jianhai Yin; Jianhai Yin; Jianhai Yin; et al. (Frontiers in Microbiology, 2018)
Clonorchiasis is an infectious disease caused by helminths of Clonorchis sinensis (C. sinensis). The adult parasite mainly inhabits the bile duct and gall bladder, and results in various complications to the hepatobiliary system. The amount of bile secreted into the intestine is reduced in cases of C. sinensis infection, which may alter the pH of the gut and decrease the amount of surfactant protein D released from the gallbladder. However, the impact of parasitic infection on the human gut microbiome remains unclear. To this end, we examined the gut microbiota composition in 47 modified Kato–Katz thick smear-positive (egg-positive) volunteers and 42 healthy controls from five rural communities. Subjects were grouped into four sub-populations based on age and infection status. High-throughput 16S rRNA gene sequencing revealed significant changes in alpha diversity between EP1 and EN1. The beta diversity showed alterations between C. sinensis-infected subjects and healthy controls. In C. sinensis infected patients, we found the significant reduction of certain taxa, such as Bacteroides and anti-inflammatory Bifidobacterium (P < 0.05). Bacteroides, a predominant gut bacteria in healthy populations, was negatively correlated with the number of C. sinensis eggs per gram (EPG, r = −0.37, P adjust < 0.01 in 20–60 years old group; r = −0.64, P adjust = 0.04 in the 60+ years old group). What’s more, the reduction in the abundance of Bifidobacterium, a common probiotic, was decreased particularly in the 60 + years old group (r = −0.50, P = 0.04). The abundance of Dorea, a potentially pro-inflammatory microbe, was higher in infected subjects than in healthy individuals (P < 0.05). Variovorax was a unique bacteria that was only detected in infected subjects. These results clearly demonstrate the significant influence of C. sinensis infection on the human gut microbiota and provided new insights into the control, prevention, diagnosis, and clinical study of clonorchiasis through the human gut microbiota.